Pediatric Mesenchymal Stem Cells Exhibit Immunomodulatory Properties Toward Allogeneic T and B Cells Under Inflammatory Conditions - Palomares Cabeza, Virginia; Hoogduijn, Martin Johannes; Kraaijeveld, Rens; Franquesa, Marcella; Witte-Bouma, Janneke; Wolvius, Eppo B.; Farrell, Eric; Brama, Pieter A. J. (Frontiers in Bioengineering and Biotechnology, 2019)
Mesenchymal stem cells from pediatric patients (pMSCs) are an attractive cell source in regenerative medicine, due to their higher proliferation rates and better differentiation abilities compared to adult MSCs (aMSCs). We have previously characterized the immunomodulatory abilities of pMSCs on T cells under co-culture. It has also been reported that aMSCs can inhibit B cell proliferation and maturation under inflammatory conditions. In this study, we therefore aimed to clarify the immunomodulatory effect of pMSCs towards T and B cells in an inflammatory microenvironment. Bone marrow derived pMSCs were primed to simulate inflammatory conditions by exposure with 50 ng/mL of IFN-γ for 3 days. To analyze the interaction between pMSCs and T cells, CD3/CD28 stimulated peripheral blood mononuclear cells (PBMCs) were co-cultured with primed or unprimed pMSCs. To investigate B cell responses, quiescent B cells obtained from spleens by CD43 negative selection were stimulated with anti-IgM, anti-CD40, IL-2 and co-cultured with either IFN-γ primed or unprimed pMSC. pMSC phenotype, B and T cell proliferation, and B cell functionality were analyzed. Gene expression of indoleamine 2,3-dioxygenease (IDO), as well as the expression of HLA-ABC, HLA-DR and the co-stimulatory molecules CD80 and CD86 was upregulated on pMSCs upon IFN-γ priming. IFN-γ did not alter the immunomodulatory abilities of pMSCs upon CD4+ nor CD8+ stimulated T cells compared to unprimed pMSCs. IFN-γ primed pMSCs but not unprimed pMSCs strongly inhibited naïve (CD19+CD27-), memory (CD19+CD27+), and total B cell proliferation. Antibody-producing plasmablast (CD19+CD27highCD38high) formation and IgG production were also significantly inhibited by IFN-γ primed pMSCs compared to unprimed pMSCs. Collectively, these results show that pMSCs have immunomodulatory effects upon the adaptive immune response which can be potentiated by inflammatory stimuli. This knowledge is useful in regenerative medicine and allogeneic transplantation applications towards tailoring pMSCs function to best modulate the immune response for a successful implant engraftment and avoidance of a strong immune reaction.